Escaping the Phagocytic Oxidative Burst: The Role of SODB in the Survival of Pseudomonas aeruginosa Within Macrophages - Cavinato, Luca; Genise, Elena; Luly, Francesco R.; Di Domenico, Enea G.; Del Porto, Paola; Ascenzioni, Fiorentina (Frontiers in Microbiology, 2020)
Reactive oxygen species (ROS) are small oxygen-derived molecules which are used to control infections by the phagocytic cells. In macrophages, the oxidative burst produced by the NOX2 NADPH-oxidase is essential to eradicate the engulfed pathogens by both oxidative- and non oxidative-killing. Indeed, while the superoxide anion (O₂ˉ) produced by NOX2, and the other ROS derived from its transformation, may directly targets the pathogen, ROS also contribute to activate non-oxidative microbicidal effectors. The response of pathogens to the phagocytic oxidative burst includes the expression of different enzymes that target ROS to reduce their toxicity. Superoxide dismutases are the primary scavenger of O2- which is transformed into H2O2. In the gram-negative Salmonella typhimurium the periplasmic SODCI has a major role in the bacterial resistance to the NOX-mediated oxidative stress. In Pseudomonas aeruginosa the two periplasmic superoxide dismutases, SODB and SODM, appear to contribute to the bacterial virulence in small animal models. Further, the NOX2-oxidative stress is essential to restrict P. aeruginosa survival in macrophages, early after infection. Here we focused on the role of the P. aeruginosa SODs in counteracting the lethal effects of the macrophagic oxidative burst. By studying the survival of the sod mutants in macrophages and by measuring ROS in the infected macrophages, we identify a dual, antagonistic, role of the SODB on P. aeruginosa survival. Indeed, the survival of sodB, but not sodM, mutants was higher than that of WT bacteria, early after infection and sodB-infected macrophages showed higher level of O2- and lower level of H2O2. This suggests that SODB contribute to produce lethal doses of H2O2 within the phagosome. But, later on after infection, sodB mutants survived less that WT bacteria, highlighting the pro-survival role of SODB. We explained this defensive role by investigating the activation of autophagy, which was higher in sodB-infected macrophages.